Cascade testing for elevated lipoprotein(a) in relatives of probands with high lipoprotein(a) - Anindita Chakraborty; Dick C. Chan; Katrina L. Ellis; Jing Pang; Wendy Barnett; Ann Marie Woodward; Mary Vorster; Richard Norman; Eric K. Moses; Gerald F. Watts (Elsevier, 2022)
Objective: Elevated lipoprotein(a) [Lp(a)] is a common inherited condition associated with cardiovascular disease. This study investigated whether cascade testing for Lp(a) was effective in detecting new cases of elevated Lp(a) in families. Methods: Relatives from adult probands with Lp(a) concentration ≥100 mg/dL were tested for elevated Lp(a) (≥50 mg/dL) via a cascade testing program in a tertiary hospital setting. The prevalence and yield of detecting new cases of elevated Lp(a) among the relatives were assessed. Results: Of the 83 probands, 43.4% had familial combined hyperlipidemia (FCHL) and 34.9% common hypercholesterolemia (CH). Among 182 relatives tested (151 adults and 31 children), elevated Lp(a) was found in 68.1%, with 32.9% having Lp(a) between 50 and 99 mg/dL and 35.2% having Lp(a) ≥100 mg/dL. One new case of elevated Lp(a) ≥50 mg/dL was identified for every 1.5 relatives tested and 1 new case of elevated Lp(a) ≥100 mg/dL for every 2.8 relatives tested. The proportion of relatives detected with elevated Lp(a) was significantly higher when tested from probands with Lp(a) >150 mg/dL compared with those with Lp(a) between 100 and 150 mg/dL (81.1% vs. 55.5%; P = 0.001). The concordance rates (kappa coefficient) for the detection of elevated Lp(a) with FCHL and CH were 34.8% (0.026) and 53.2% (0.099), respectively. Conclusion: Cascade testing for elevated Lp(a) from affected probands with phenotypic dyslipidemia is highly effective in identifying new cases of high Lp(a) in families. The yield of detecting elevated Lp(a) is greater when probands have higher levels of Lp(a) and exceeds the detection of relatives with FCHL and CH.